The impact of physical activity on social support among Chinese college students: the mediating role of physical self-esteem and the moderating effect of gender - Wang, Jingyi; Wei, Baojian; Cai, Shichang; Jiang, Hui (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to examine the mechanisms through which physical activity influences social support among Chinese college students by constructing a moderated mediation model, with physical self-esteem as a mediator and gender as a moderator.MethodsA total of 667 undergraduates and postgraduates (327 males, 340 females) from a comprehensive university in Jiangsu Province were recruited using cluster convenience sampling. Physical activity (PARS-3), physical self-esteem (College Students’ Physical Self-Esteem Scale), and social support (Adolescent Social Support Rating Scale) were measured via structured questionnaires. Multi-level statistical analyses were conducted using the SPSS PROCESS macro to test mediation and moderated mediation effects.Results(1) Physical activity significantly and positively predicted social support (β = 0.06, p < 0.001); (2) Physical self-esteem partially mediated this relationship, with an indirect effect of 0.02, accounting for 33.33% of the total effect; (3) Gender significantly moderated the pathway between physical activity and social support. Among females, the effect was significantly positive (β = 0.12, p < 0.001), whereas among males, the effect was negative (β = −0.05, p < 0.001).ConclusionThese findings demonstrate that physical activity enhances social support both directly and indirectly through increased physical self-esteem, while gender differences shape the strength and direction of this relationship. Specifically, physical activity benefits female students’ social support but may reduce that of male students, possibly due to the competitive orientation of their sports participation. The study extends social integration and self-perception theories and highlights the importance of gender-sensitive interventions in university-based physical activity and mental health programs.